Multistability of Bi-Reaction Networks (CSIAM Transactions on Applied Mathematics, 2025)
We provide a sufficient and necessary condition in terms of the stoichiometric coefficients for a bi-reaction network to admit multistability. Also, this result completely characterizes the bi-reaction networks according to if they admit multistability.
Keywords: Reaction networks; mass-action kinetics; multistationarity; multistability